Digital Transformation in Human Resource Management and Its Role in Gen Z Career Development: A Systematic Literature Review - Immanuella Anita Indroputri; Regi Sanjaya (Master of Management, School of Business and Management, Petra Christian University, 2024)
With an emphasis on the career development of Gen Z, this systematic literature review explores the relationship between digital transformation and HRM. This study reveals the significant influence of digital technology on HRM practices, especially in areas like hiring, talent management, performance reviews, and staff development. This is achieved through rigorous screening and analysis using the Systematic Literature Review (SLR) to thoroughly address our research questions by systematically locating, assessing, and interpreting key findings from relevant studies of the chosen 19 key studies from 306 unique documents generated. The results show digital transformation's critical role in determining Gen Z workers’ career paths and the necessity for firms to modify their HRM strategies and practices to engage and support this generation of digital natives effectively.